2021
DOI: 10.1093/rheumatology/keab827
|View full text |Cite
|
Sign up to set email alerts
|

Disparity in peripheral and renal B-cell depletion with rituximab in systemic lupus erythematosus: an opportunity for obinutuzumab?

Abstract: Objectives To investigate key factors that may contribute to the variability of rituximab-mediated peripheral and renal B cell depletion (BCD) in Systemic Lupus Erythematosus (SLE). Methods We analysed: 1) CD19+ B cell counts in patients with SLE before and one, two, three and six months after treatment with rituximab, comparing them with Rheumatoid Arthritis (RA) patients; 2) the presence of B cells in renal biopsies after r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…This duration-associated dampened humoral immune response may further lead to a discrepant response to B-cell-targeted therapies. Recently, a small study found that SLE patients with longer durations had difficulties achieving complete depletion of peripheral B cells ( 18 ), and a small observation shows that a shorter duration of LN responds better to rituximab ( 19 ). Our findings merits more detailed profiling of B cell in duration courses, especially the balance of physiological/pathological B cells, which may give a better interpretation of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…This duration-associated dampened humoral immune response may further lead to a discrepant response to B-cell-targeted therapies. Recently, a small study found that SLE patients with longer durations had difficulties achieving complete depletion of peripheral B cells ( 18 ), and a small observation shows that a shorter duration of LN responds better to rituximab ( 19 ). Our findings merits more detailed profiling of B cell in duration courses, especially the balance of physiological/pathological B cells, which may give a better interpretation of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, 1 month after the first infusion of rituximab (1 g administered on day 1 and 15), the inguinal lymph nodes of rheumatoid arthritis patients show the persistence of several B‐cell follicular structures and the persistence of memory B cells 56 . Residual B cells have also been described in the synovium from patients with rheumatoid arthritis, 57–59 salivary glands of patients with Sjögren syndrome 60 and renal biopsy samples of SLE patients with lupus nephritis 61 …”
Section: Rituximab‐resistant B Cells May Explain Relapses After Initi...mentioning
confidence: 97%
“…56 Residual B cells have also been described in the synovium from patients with rheumatoid arthritis, [57][58][59] salivary glands of patients with Sjögren syndrome 60 and renal biopsy samples of SLE patients with lupus nephritis. 61 Strikingly, none of the residual B cells have detectable surface expression of CD20. The absence of CD20 expression is in part due to epitope masking, but is also contributed to by antigen modulation through CD20 internalization [62][63][64] or trogocytosis [65][66][67][68] (Figure 1).…”
Section: R It U X I M a B -R E Sista N T B Ce L L S M Ay E X Pl A I N...mentioning
confidence: 99%
“…Obinutuzumab is more effective at evoking Fcγ receptor-mediated effector mechanisms as compared with rituximab. It was superior to rituximab at inducing B-cell depletion [26]. More clinical trials are needed to confirm its availability in clinical application in the future.…”
Section: Obinutuzumabmentioning
confidence: 97%